Stochastic Coulomb blockade and scaling of charging energy in a double quantum dot system - Molenkamp, Laurens W.; Kemerink, Martijn (Superlattices and microstructures, 2009)
We have studied the transport properties of a device consisting of two quantum dots, defined electrostatically in a (Al.Ga)As heterostructure. In the series conductance of the two dots, we observe irregularly spaced conductance peaks of fluctuating amplitude. This behaviour results from transport in the stochastic Coulomb blockade regime. In a second experiment, we measure the charging energy of one dot through the effect of its potential (which varies in a saw-tooth fashion with gate voltage) on the conductance of the other dot. We find that the charging energy scales quadrat-ically with the reflection probability of the tunnel barriers, in agreement with a recent theory.